Risālah dar Ādāb al-Tarīqah: as a contribution to the contemporary sufism - Mansurov, Fatkhiddin; Noor Azlinda, Zainal Abidin (2017)
Khawaja Yusuf Hamadānī (d. 535/1140), a prominent scholar and Sufi, played a significant role in the formation of Sufism. His works are written in accordance with the Qur’an and Sunna, mainly cover the issues of Aqīdah (belief system in Islam), Akhlāq (good manners) and principles of Tasawwuf (Sufism). One of the imported works of Hamadānī is Risālah dar Ādāb al-Tarīqah (An Epistle of the Sufi Order’s Proprieties). This short epistle is written in Persian, concerning good and proper conducts in Tasawwuf and original manuscript kept at Istanbul Millet Library Turkey, under registry number 1028. The work is about the important principles of Tasawwuf which are must be carried out by Sufi followers. Such as, importance of reading book, uzlah (seclusion), controlling of the nafs’s (self, ego) desires, dining and sleeping proprieties, halal food, clothing and housing. The main objective of the research is to do full translation of this epistle into English and to investigate a few major points of the author’s doctrine. Moreover, this study and translation of the epistle could be one of significant contribution to the contemporary Sufism.